Effects of low-protein diet on renal oxidative stress, biochemistry and histology in weaned rats - Yee, Xin Lee; See, Meng Lim; Xin, Qian Ng; Pei, Teng Lum; Elvy Suhana Mohd Ramli; Chin, Kok-Yong; Siti Balkis Budin (Penerbit Universiti Kebangsaan Malaysia, 2025)
A low-protein diet (LPD) leads to low plasma protein and insufficient building blocks for normal kidney development, especially in children. This study aimed to determine the effects of short-term LPD on renal oxidative stress, biochemical profile and histologic changes in weaned rats. Three-week-old male and female Sprague Dawley rats were divided into the LPD group and the normal protein diet (NPD) group for 3 weeks. Renal oxidative stress, biochemical profile and histology were examined. Both male and female rats had significantly (p<0.05) lower body weight, smaller kidneys and higher advanced oxidation protein product concentrations after a 3-week LPD. Only LPD-fed females had lower malondialdehyde concentrations and superoxide dismutase activity but higher reduced glutathione concentrations compared to NPD-fed females. Histologic examination showed abnormal histologic features in the proximal and distal tubules, fibrosis in the cuboidal cells, reduced lumen diameter, smaller glomerular tuft area and glomerular tuft volume in LPD-fed male and female groups. In conclusion, short-term protein malnutrition leads to renal injury in male and female weaned rats. The different responses of male and female rats to protein malnutrition suggest sexual dimorphism and hormonal factors in kidney development, with females showing a higher susceptibility to oxidative damage.